2012
DOI: 10.1016/j.jpeds.2011.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Replication of a Genome-Wide Association Study of Birth Weight in Preterm Neonates

Abstract: Objective To examine associations in a preterm population between rs9883204 in ADCY5 and rs900400 near LEKR1 and CCNL1 with birth weight. Both markers were associated with birth weight in a term population in a recent genome-wide association (GWA) study by Freathy et al. Study design A meta-analysis of mother and infant samples was performed for associations of rs900400 and rs9883204 with birth weight in 393 families from the U.S., 265 families from Argentina and 735 mother-infant pairs from Denmark. Z score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…The study population consisted of children from a previous case–control study nested in the Danish National Birth Cohort (DNBC) with available DNA and detailed information on skin diseases (http://www.dnbc.dk). In the earlier study, living singletons born preterm (cases, n = 1000, ≤36 weeks) and term (controls, n = 1000, 40 weeks) from uncomplicated pregnancies were selected for genomewide association study .…”
Section: Methodsmentioning
confidence: 99%
“…The study population consisted of children from a previous case–control study nested in the Danish National Birth Cohort (DNBC) with available DNA and detailed information on skin diseases (http://www.dnbc.dk). In the earlier study, living singletons born preterm (cases, n = 1000, ≤36 weeks) and term (controls, n = 1000, 40 weeks) from uncomplicated pregnancies were selected for genomewide association study .…”
Section: Methodsmentioning
confidence: 99%
“…Mutations in factor V Leiden, prothrombin G20210A, and IL1β have been implicated in the development of grade I and II IVH. 7072 Polymorphisms of IL-6 and TNFα are proposed as genetic modifiers of IVH risk. 73, 74 In addition, polymorphism of methylene tetrahydrofolate reductase (MTHFR) gene has been reported in infants with IVH.…”
Section: Pathogenesis Of Intraventricular Hemorrhagementioning
confidence: 99%
“…In their meta-analysis of five independent Caucasian preterm infant populations, Ryckman et al (2012) confirmed a marginally significant association between rs900400 and birth weight. However, the influence of rs9883204 and rs900400 on birth weight varies among people of different regions and races.…”
Section: Introductionmentioning
confidence: 89%